CD5L Promotes M2 Macrophage Polarization through Autophagy-Mediated Upregulation of ID3 - Sanjurjo, Lucía; Aran, Gemma; Téllez, Érica; Amézaga, Núria; Armengol, Carolina; López, Daniel; Prats, Clara; Sarrias, Maria-Rosa (Frontiers in Immunology, 2018)
CD5L (CD5 molecule-like) is a secreted glycoprotein that controls key mechanisms in inflammatory responses, with involvement in processes such as infection, atherosclerosis, and cancer. In macrophages, CD5L promotes an anti-inflammatory cytokine profile in response to TLR activation. In the present study, we questioned whether CD5L is able to influence human macrophage plasticity, and drive its polarization towards any specific phenotype. We compared CD5L-induced phenotypic and functional changes to those caused by IFN/LPS, IL4 and IL10 in human monocytes. Phenotypic markers were quantified by RT-qPCR and flow cytometry, and a mathematical algorithm was built for their analysis. Moreover, we compared ROS production, phagocytic capacity and inflammatory responses to LPS. CD5L drove cells towards a polarization similar to that induced by IL10. Furthermore, IL10- and CD5L-treated macrophages showed increased LC3II content and colocalization with acidic compartments, thereby pointing to the enhancement of autophagy-dependent processes. Accordingly, siRNA targeting ATG7 in THP1 cells blocked CD5L-induced CD163 and MERTK mRNA and efferocytosis. In these cells, gene expression profiling and validation indicated the upregulation of the transcription factor ID3 by CD5L through ATG7. In agreement, ID3 silencing reversed polarization by CD5L. Our data point to a significant contribution of CD5L-mediated autophagy to the induction of ID3 and provide the first evidence that CD5L drives macrophage polarization.